Análisis del procedimiento de identificación en el área de admisión y registro de pacientes del Centro Médico Santa Rosa - Mayorga Cercado, Vanessa Jacqueline (2021)
The organization and control of each of the areas of a company must be carried out with caution and in the best possible way, in this way the fulfillment of the institutional objectives has to be carried out at 100%, this work is focused on the procedure of identification in the area of admission and registration of patients of the Santa Rosa Medical Center, the same one that has presented certain problems this creating many times that the Medical Center has economic losses, in this case study we will talk about the two most common ways of committing these errors, the same ones that are due to human error or lack of updating of the system, and that both can be corrected with the respective internal administrative control by the Patient Admissions department.